2008
DOI: 10.1016/j.juro.2007.11.063
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Local Tumor Control on Distant Metastases and Cancer Related Mortality After External Beam Radiotherapy for Prostate Cancer

Abstract: Purpose-We report local control outcomes, as assessed by posttreatment biopsies in patients who underwent 3-dimensional conformal radiotherapy for clinically localized prostate cancer. In addition, we report the influence of local tumor control on long-term distant metastases and cause specific survival outcomes.Materials and Methods-Posttreatment prostate biopsies were performed in 339 patients who underwent 3-dimensional conformal radiotherapy for clinically localized prostate cancer. The histological outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(103 citation statements)
references
References 14 publications
7
95
0
1
Order By: Relevance
“…Of the three patients who developed Grade 3 urinary toxicity, two were characterized at baseline as having Grade 2 symptoms, and one patient was classified as having Grade 1 symptoms at baseline. The median IPSS at baseline was 6 (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], and the median IPSS at last followup was 12 (range, 1-30). Resolution of an elevated IPSS was seen in 41% of patients (returned within 2 points of baseline) within a median time of 4.5 months.…”
Section: Toxicity Outcomesmentioning
confidence: 99%
“…Of the three patients who developed Grade 3 urinary toxicity, two were characterized at baseline as having Grade 2 symptoms, and one patient was classified as having Grade 1 symptoms at baseline. The median IPSS at baseline was 6 (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], and the median IPSS at last followup was 12 (range, 1-30). Resolution of an elevated IPSS was seen in 41% of patients (returned within 2 points of baseline) within a median time of 4.5 months.…”
Section: Toxicity Outcomesmentioning
confidence: 99%
“…Zelefsky et al demonstrated that 10-year PSA relapse-free survival was 59% for patients with negative biopsies, compared to 49% for those with severe treatment effect and only 3% for those with NTE on biopsy. 10 Although the patients with severe treatment effect Number of cores total, median (IQR) 11 ( had lower 10-year PSA survival rates, this was not statistically significant and did not correlate with metastasis-free survival or CSS. Vance et al looked at the clinical outcome of patients based on routine biopsy at two years as stratified by those with negative (no cancer), atypical/suspicious cells (not diagnostic of carcinoma), CTE, and NTE.…”
Section: Discussionmentioning
confidence: 90%
“…Many studies have shown increased incidence of local recurrence, distant metastasis, and death from prostate cancer for those patients with a positive post-radiation biopsy (11,12). Our retrospective study specifically examined outcomes for patients with a negative post-radiation prostate biopsy.…”
Section: Commentsmentioning
confidence: 99%